Respostas

2014-06-24T21:17:15-03:00
A)  23 x - 16 = 14 - 17 x
23x + 17x = 14 + 16
40x = 30
x = 30/40
x = 3/4

B)
10 x - 5 (1+x) = 3 (2 x - 2) - 20 
10x -5 - 5x = 6x - 6 - 20
10x - 5x - 6x = -6 - 20 + 5
-1x = -21
x = 21

C)
13 x -1 = 1 - 3 x + 11 
13x + 3x = 1 + 11 + 1
16x = 13
x = 13/16

D)
5 x - 5 + x = 9 + x
5x + x - x = 9 + 5
5x = 14
x = 14/5

E) 7 x - 20 = 2 x - 2 
7x - 2x = -2 + 20
5x = 18
x = 18/5

F) 6x - 40 = 60 (x - 5 )
6x - 40 = 60x - 300
6x - 60x = -300 + 40
-54x = -260
x = 260/54
x = 130/27